Sleep quality and frequency of comorbidities and its relation with chronic migraine related disability in patients with chronic migraine (Annals of Medical Research, 2021)
Aim: Detecting quality of sleep and relation of comorbid situations that may effect sleep quality such as anxiety, depression, sleep apnea and excessive daytime sleepiness (EDS) with chronic migraine in patients with chronic migraine. Material and Methods: 21 patients diagnosed with chronic migraine according to ICHD-3 Beta and 21 healthy volunteers as age and gender matched control group were included. Migraine type, duration, frequency of attacks in a month, Visual Analogue Scale (VAS), Migraine Disability Assessment Scale (MIDAS) scores of the migraine patient group were calculated. Beck Depression Inventory (BDI), Hamilton Anxiety Rating Scale (HAM-A), Pittsburgh Sleep Quality Index (PSQI), Berlin Questionnaire (BQ), Epworth Sleepiness Scale (ESS) and Stanford Sleepiness Scale (SSS) were applied to every study participants. Scores of the chronic migraine patients from scales were compared to the ones of healthy controls. In addition, the relation between scores of the chronic migraine patients from scales and MIDAS score was studied.Results: PSQI, ESS, HAM-A and BDI scores of the chronic migraine patients were detected to be significantly higher than of the healthy individuals (p0.001, 0.004, 0.001, 0.021 subsequently). Chronic migraine patient group had a significantly higher risk of sleep apnea compared to healthy individuals according to BQ (p=0.015). A positive significant correlation was detected between chronic migraine related disability and EDS of patients with chronic migraine ((p=0.034), (r=0.465)).Conclusion: Sleep quality has been deteriorated due to headache in patients with chronic migraine. There is a strong relation between chronic migraine and comorbid conditions such as anxiety, depression, EDS, increased sleep apnea risk. Only EDS increases chronic migraine related disability.
Keywords: Chronic migraine; chronic migraine comorbidities; sleep quality; anxiety; depression; sleep apnea; chronic migraine related disability